Autonomous Trajectory Tracking for Ground and Marine-Surface Vessels Using L1 Controller - Anuwatpanich, Khunakon; Prempraneerach, Pradya (Frontiers in Engineering Innovation Research, 2019)
This research paper presents studies of applying autonomous trajectory-tracking logic for 4-wheel car robot and catamaran robot using an L1 controller. A trajectory computation toward specified target points need to calculate a centripetal-acceleration command, described by distance (L1) and damping ratio (x) parameters, such that vehicle can approach the desired straight-path trajectory. Effect of three parameters: 1) L1, 2) x and 3) proportional gain (Kps) of a PID control for steering, on efficiency of autonomous trajectory tracking of both vehicles are evaluated from 1) an average error of a perpendicular distance from vehicle toward the specified path or average cross-track error and 2) an average maximum error of overshoot from specified path. Experiments of autonomous trajectory tracking reveal that 4-wheel robot car, governed by the L1 controller, approaches desired trajectory similar to an overdamped response. Robot car trajectory is not sensitive to L1 and x parameter variations because a 4-wheel car dynamic has good traction capability during a sharp turn. On the contrary, catamaran can slideways in water because of small hydrodynamics drag force. As a result, L1, x, Kps, variations have strong effects on a performance of the autonomous trajectory tracking. Using small L1 and Kps, catamaran can track specified straight trajectories automatically with good performance